RESEARCH ON THE CORRELATION BETWEEN SOCIAL DESIRABILITY AND VALUE ORIENTATIONS IN ADOLESCENCE - Alyona Volodymyrivna Shevchenko (Insight: the psychological dimensions of society, 2019)
Abstract. The study underlines that everyone has his/her value system which is developed over the course of a lifetime, reinterpreted and modified. It highlights that the most important period for creating and developing a value system is adolescence, when priorities undergo essential changes and transformations partly under the pressure of “significant others” and society. The behavior of a young person who does not contradict others, generally accepted norms and values not to differ from majority, agrees to other people’s views and opinions, transforming his/her value system, is considered as socially desirable.The purpose of the study is to conduct theoretical research on the correlation between the phenomenon of social desirability and value orientations of adolescents.The following methods are used in the research: analyzing of scientific literature on the issues outlined; systematization and generalization; substantiation of correlations between social desirability and value orientations of adolescents.Results: the problem of the impact of social desirability on value orientations of adolescents has been examined in the paper. Scientific studies of the leading Ukrainian and foreign scholars have been analyzed. The peculiarities of formation of value orientations of adolescents have been illuminated. The research looks at the features of developing value orientations. The influence of the phenomenon of “social desirability” on personality has been described. A number of factors that determine the social desirability effect are indicated, methods of manifestation and control of the social desirability effect have been revealed.Conclusions: An understanding of the depth and complexity of the relationship between social desirability and value orientations has outlined. It has been stated that that values are developed over the course of a lifetime and are inclined to be changed and modified. It has been emphasized that at a young age there are significant transformations in the value-sense sphere of the individual.